UNDERSTANDING THE RULES OF LANGUAGE ACQUISITION IN CHILDREN BASED ON THE NATURAL GRAMMAR'S THEORY BY CHOMSKY: A REVIEW OF LITERATURE - Ani Agus Riani (LP2M IAIN Sultan Amai Gorontalo, 2016)
Rules of language acquisition in children based on